Investigating Constraints Along the Plant Secretory Pathway to Improve Production of a SARS-CoV-2 Spike Vaccine Candidate - Margolin, Emmanuel; Verbeek, Matthew; de Moor, Warren; Chapman, Ros; Meyers, Ann; Schäfer, Georgia; Williamson, Anna-Lise; Rybicki, Edward (Frontiers in Plant Science, 2022)
Given the complex maturation requirements of viral glycoproteins and the challenge they often pose for expression in plants, the identification of host constraints precluding their efficient production is a priority for the molecular farming of vaccines. Building on previous work to improve viral glycoprotein production in plants, we investigated the production of a soluble SARS-CoV-2 spike comprising the ectopic portion of the glycoprotein. This was successfully transiently expressed in N. benthamiana by co-expressing the human lectin-binding chaperone calreticulin, which substantially increased the accumulation of the glycoprotein. The spike was mostly unprocessed unless the protease furin was co-expressed, despite the inclusion of an enhanced furin cleavage site (RRRRRR). Co-expression of several broad-spectrum protease inhibitors did not improve accumulation of the protein any further. The protein was successfully purified by affinity chromatography and gel filtration, although the purified product was heterogenous and the yields were low. Immunogenicity of the antigen was tested in BALB/c mice, and cellular and antibody responses were elicited after low dose inoculation with the adjuvanted protein. This work constitutes an important proof-of-concept for host plant engineering in the context of rapid vaccine development for SARS-CoV-2 and other emerging viruses.